Evaluation and Analysis of Cruise Tourism Developing Strategies in Shandong, China - Feng, Xiaonan; Dai, You-Yu (Journal of Tourism Management Research, 2020)
Cruise tourism in China brings many tourism benefits to the local area. However, the cruise tourism market is facing a slowdown in growth. Based on the current situation of the cruise tourism market in China, this paper uses the PEST embedded SWOT analysis method to analyze the Chinese cruise tourism market and explore the potential problems to promote its growing. The findings are, in addition to the construction of dedicated cruise terminal as soon as possible, perfecting the relevant supporting facilities, the basis of Shandong diversification, innovation should be encouraged to attract qualified international cruise lines or investment developers cruise homeport development and construction, and take unified development pattern of the construction of the wharf and the surrounding areas, with other facilities earnings in its terminal yield, improve the enthusiasm of enterprise construction of pier. In summary, the improvement of the cruise industry service chain, the training of cruise professionals, the optimization of cruise tourism products, and the specific policy recommendations for the role of the cruise industry association are all discussed.